The European Second Generation Compared Does the Integration Context Matter? - Lelie, Frans; Crul, Maurice; Schneider, Jens (IMISCoe Research Series, 2012)
Integration of newcomers is a foremost challenge for contemporary Europe. The 'second generation' - children born of immigrant parentage - is crucial in this process, for they constitute a growing and increasingly vocal segment of the metropolitan youth. This book offers an unprecedented look at the real-life place and position of the European second generation in education, labour, social relations, religion and identity formation. Using data collected by the TIES survey in fifteen cities across eight European countries, the authors paint a vivid picture of how the children of immigrants from Turkey, Morocco and former Yugoslavia are progressing. Their findings and cross-national comparisons are demographically compelling and at times revelational.